Helping Relationships in Mental Health - Morgan, Steve. author. aut Link
XI, 201 p.
Keywords: How do you respond to the distress of a man who is sitting before you, in his own flat, towels draped around his shoulders, newspaper wedged beneath the brim of his hat, an upturned frying pan over his hat and a partially filled washing-up bowl balanced on top of the frying pan? He holds the bowl with one hand and a cigarette in the other, while he force fully proclaims the secret services have placed someone in the flat above to drop radioactive dust down on him all day and all night. To start with, you could offer him a light for his cigarette. The most likely medical response would be to consider increasing his antipsychotic medicine, though a cursory glance at his medical history suggests that inpatient admissions and large mUltiple prescriptions of injections and tablets have failed to eradicate the distressing fears that the secret services have occupied the ward above. Perhaps all the increased medication will achieve is to stop him going upstairs intent on retribu tion. It may even leaden his limbs sufficiently to make his current balanc ing act too difficult to sustain.